When Unemployment Disappears: Ireland in the 1990s - Brendan Walsh (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper examines the behaviour of the Irish labour market during the 1990s. Over the course of the decade the Irish unemployment rate fell from the highest to the lowest in the EU. Over the same period a record number of jobs was created and all the indicators suggest that full employment was achieved. The primary reason for this employment miracle was the output boom, which in turn may be attributed to Ireland's super competitiveness in the late 1990s. Several factors contributed to this - a low exchange rate, the inflow of FDI to high productivity sectors, and wage moderation following the return to centralised wage agreements in 1987. Labour market reforms, including a tightening of the social welfare regime and a switch of spending from income support to active labour market policies, played a positive role. The fact that unemployment has risen only slowly during the current downturn points to the lasting effect of these changes.
Keywords: 330